Resource margin accounting: An elucidation and preliminary empirical testing - JOHNSON, Peter (Institutional Knowledge at Singapore Management University, 2007)
The aim of this paper is to describe “resource margin accounting” (RMA) as a valuation framework in strategic analysis. The paper defines RMA as an improved framework for valuation in competitive strategy, relative to existing value-added and cash flow methods. The framework was tested on a sample of 300 US manufacturing companies between 1983 and 1998. The paper finds that the resource margin approach has greater explanatory power than traditional market-to-book valuation measures. The resource margin approach is methodologically and empirically superior to economic value-added (EVA) and cash flow models of valuation. The paper presents and tests a new valuation method: RMA.